2017
DOI: 10.3390/f9010013
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Wood Quality of Douglas Fir and Spruce from Afforested Agricultural Land and Permanent Forest Land in the Czech Republic

Abstract: This study compares the quality of wood from two distinct sites in the Czech Republic-from former afforested agricultural land and forest land. We compared the properties of Norway spruce wood (Picea abies Karst.) and Scots pine wood (Pinus sylvestris L.), the most important domestic tree species, to Douglas fir (Pseudotsuga menziesii (Mirbel) Franco), a North American tree species and a potential substitute for the domestic spruce. Wood density, modulus of elasticity (MOE), modulus of rupture (MOR) and impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…menziesii was found to be suitable for European forests [1,2]. High growth rates [3][4][5], good wood quality [6], resistance against fungal pathogens and low numbers of pests and diseases [7] are factors that have contributed to the current widespread distribution of Douglas fir in European forests [8]. This tree's value in the coming years is likely to increase further [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…menziesii was found to be suitable for European forests [1,2]. High growth rates [3][4][5], good wood quality [6], resistance against fungal pathogens and low numbers of pests and diseases [7] are factors that have contributed to the current widespread distribution of Douglas fir in European forests [8]. This tree's value in the coming years is likely to increase further [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Site index: Expressed as a mean stand height at the age of 100 years 5. TRW: Tree-ring width 6. EPS: Expressed population signal.…”
mentioning
confidence: 99%
“…Similar increase of smaller magnitude in cumulative ΔW by less than 50% was observed for L. decidua in 2018. We assume that the lower interannual changes in cumulative ΔW of P. sylvestris and L. decidua result from lower elasticity of their tissues due to their higher wood density (Požgaj et al, 1993;Zeidler et al, 2018). González-Rodríguez et al (2017) have shown that stem diameter shrinkage is mainly determined by sap flow changes.…”
Section: Seasonal Development Of Stem Growth and Tree Water Statusmentioning
confidence: 99%
“…The environmental variance related to the geographical origin from post-agricultural lands and post-forest lands was analysed for Scots pine (Pinus sylvestris L.), Douglas fir (Pseudotsuga menziesii (Mirb.)) and Norway spruce wood [16,17]. Higher technical quality (by means of the mechanical properties of wood) was identified in the case of wood from forest lands, compared to post-agricultural lands.…”
Section: Introductionmentioning
confidence: 99%